Gandhi, Lohia & Deendayal - Parameswaran, P., 1927- (Deendayal Research Institute, 1978)
Essays on the common bases of Mohandas Karamchand Gandhi, 1869-1948, Rammanohar Lohia, 1910-1967, and Deendayal Upadhyaya, 1916-1968.